Pola Kemitraan Usaha Tani Kelapa Sawit Kelompok Tani Telaga Biru dengan PT. Sawindo Kencana melalui Koperasi di Kabupaten Bangka Barat Provinsi Bangka Belitung - SAPUTRA, I MADE GANNAL DWI; ANGGRENI, I G A A LIES; DHARMA, I PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.6, No.2, April 2017DO - 10.24843/JAA.2017.v06.i02.p08, 2017)
Farming Partnership of Palm Oil Farmers Group of Telaga Biru, with PT. Sawindo Kencana in West Bangka of Bangka Belitung. This research is to determine the mechanism of partnership between PT. Sawindo Kencana with farmer groups of Telaga Biru through cooperatives, farmers' rights and obligations and the company as well as the role of the position of the institutions concerned, the effectiveness of cooperation, and obstacles encountered in the course of the partnership. Location of research was selected by using purposive sampling. The type of data includes quantitative and qualitative data derived from primary and secondary data. Methods of data collection are interviews and documentation. Data analysis was conducted by using qualitative and quantitative descriptive method. The research results showed that the mechanism of implementation of the partnership based on a written agreement between farmers' groups of Telaga Biru and PT. Sawindo Kencana already realized well. The rights of farmers are to obtain the seeds, fertilizers, crop tool, material of pesticides, and marketing of the crop. The rights of the company is to obtain the harvest from farmers. Obligations of farmers namely provide crop yields of quality palm oil. The company's obligation namely to provide the needs of farmers such as fertilizer, harvesting equipment, materials of pesticides, and crop yields rights. The effectiveness of cooperation, namely the certainty of the role of the farmer groups of Telaga Biru in the company in partnership was not running optimally, but the certainty of the role of the company is already well underway. Obstacles in the farmer group of Telaga Biru namely that the farmers ‘background is different, lacking the discipline of saving money, and lack of participation in the care of smallholdings.
Keywords: partnership pattern, palm oil, mechanism